Effect of intense endurance training with egg white and wheat germ supplementation on cardiopulmonary function in endurance runners - Abdollah Niloufari; Foad Feizolahi; Fariba Aghaei; Mahsa Mohsenzadeh (Journal of Exercise & Organ Cross Talk)
This study investigated the effects of intense endurance training (HIET) combined with egg white and wheat germ supplementation on immune, respiratory, and cardiopulmonary function in endurance runners. In this quasi-experimental study, 24 male endurance runners from Saqqez City were randomly assigned to either a training + supplement group (n=12) or a training + placebo group (n=12). Both groups underwent 8 weeks of HIET (3 sessions/week, 60 min/session, 70-90% heart rate reserve). The supplement group consumed 15g egg white powder (75 kcal) and 17.5g wheat germ powder (78 kcal) daily, approximately 2 hours before training. The placebo group received starch powder. Cardiopulmonary function (VO2max, FEV1), cardiac biomarkers (NT-proBNP, left ventricular stroke volume - LVSV), and inflammatory markers (IL-6) were assessed pre- and post-intervention. Data were analyzed using ANCOVA (SPSS v26, α=0.05), controlling for baseline values. Significant improvements were observed in the supplement group compared to the placebo group for VO2max (F(1,21)=29.482, p<0.001, η²=0.510) and FEV1 (F(1,21)=60.308, p<0.001, η²=0.742). IL-6 levels decreased significantly in the supplement group relative to the placebo group, which showed an increase (F(1,21)=7.848, p=0.011, η²=0.272). No significant between-group differences were found for NT-proBNP (F(1,21)=3.627, p=0.071, η²=0.147) or LVSV (F(1,21)=0.061, p=0.807, η²=0.003). Eight weeks of HIET combined with egg white and wheat germ supplementation significantly enhanced maximal oxygen consumption and expiratory function while attenuating exercise-induced inflammation in endurance runners, compared to HIET alone. These findings suggest potential benefits of this supplement combination for improving cardiopulmonary performance and modulating immune responses during intense endurance training.